Deep Western Boundary Current transport variability in the South Atlantic: Preliminary results from a pilot array at 34.5° S - Meinen, C. S. (2012)
The first direct estimates of the temporal variability of the absolute transport in the Deep Western Boundary Current (DWBC) at 34.5° S in the South Atlantic Ocean are obtained using just under one year of data from a line of four pressure-equipped inverted echo sounders. Hydrographic sections collected in 2009 and 2010 confirm, based on neutral density, temperature, salinity, and oxygen values, the presence of the DWBC, one of the main deep pathways of the Meridional Overturning Circulation. Both data sets indicate that the DWBC reconstitutes itself after breaking into eddies in the western sub-tropical Atlantic near 8° S. The amplitude and spectral character of the DWBC transport variability are comparable with those observed in the North Atlantic, where longer records exist, with the DWBC at 34.5° S exhibiting a transport standard deviation of 25 Sv and variations of ∼ 40 Sv occurring within periods as short as a few days. There is little indication of an annual cycle in the DWBC transports, although the observational records are too short to be definitive. A Monte Carlo-style analysis using 27 yr of model output from the same location as the observations indicates that about 48-60 months of data will be required to fully assess the deep transport variability. The model suggests the presence of an annual cycle in DWBC transport, however its statistical significance with even 27 yr of model output is low, suggesting that seasonal variations in the model are weak.